Strategi inkulkasi guru PAI dalam pembentukan sikap sopan santun pada siswa di sekolah menengah pertama - Al ‘Iffah, Aulia; Subando, Joko (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This study explores the strategies employed by Islamic education teachers to cultivate students’ politeness at the junior high school level within character education based on moral and religious values. Using a descriptive qualitative approach, data were obtained through observations, interviews, and documentation. The results indicate that the development of politeness is supported by emotional and instructional strategies. Emotional strategies include creating a positive learning environment, being sensitive to students’ needs, appreciating their feelings, and respecting their perspectives. Instructional strategies involve the use of interactive learning media, motivational feedback, and simple, communicative language suited to students’ understanding. Overall, the study highlights the essential role of teachers as role models in fostering polite behavior through emotional engagement and effective communication.